2015
DOI: 10.1615/interfacphenomheattransfer.2015013344
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermo-Capillary Flow Inside an Evaporating Pinned Water Droplet

Abstract: International audienceThermo-capillary flow inside an evaporating water drop on heated or non-heated substrate is investigated. The modeling of the internal flow inside the drop takes into account the effects of the privileged evaporation near the contact line as well as thermo-capillarity. Heat transport equations by convection-diffusion in the drop, conduction in both solid and gas phases, and vapor diffusion in the surrounding air are solved numerically in a quasi-steady state. Results showed that the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…We thus do not expect strong Marangoni flow in our experiment. This was also pointed out by Xiao et al [26] and Bouchenna et al [24], who found the influence of the thermo-capillary effect on the evaporation of a sessile droplet negligible at ambient temperatures.…”
Section: Modelssupporting
confidence: 70%
See 1 more Smart Citation
“…We thus do not expect strong Marangoni flow in our experiment. This was also pointed out by Xiao et al [26] and Bouchenna et al [24], who found the influence of the thermo-capillary effect on the evaporation of a sessile droplet negligible at ambient temperatures.…”
Section: Modelssupporting
confidence: 70%
“…The importance of those flows can be estimated by the Marangoni Ma number [24],Ma=(normal∂γ/normal∂T)ΔThμαT,where γ is the surface tension, Δ T the temperature difference, h the characteristic length, μ the dynamic viscosity of the liquid and α T the thermal diffusivity of the liquid. For pure water, ∂ γ /∂ T = 1.56 × 10 −4 kg s −2 K −1 [25], Δ T ≃ 0.1 K, μ = 1.0 × 10 −3 kg −1 m −1 s −1 and α T = 1.43 × 10 −7 m 2 s −1 and a bridge in contact between two walls, h = z 1 /2 ≃ 0.75 10 −3 m, the Marangoni number is Ma ≃ 80.…”
Section: Modelsmentioning
confidence: 99%
“…The mathematical formulation based on conservation equations, i.e., mass, momentum, energy, and particles concentration is written in a general form (Ait Saada et al, 2010, 2013Bouchenna et al, 2015). The flow inside the droplet is governed by the Navier-Stokes equations; it is induced by the strong evaporation rate at the contact line, the thermo-capillarity, and the thermal buoyancy.…”
Section: Problem Statement and Mathematical Formulationmentioning
confidence: 99%
“…The associated dimensionless boundary conditions are indicated in Fig. 1 and the dimensionless conditions at interfaces are written as (Bouchenna et al, 2015):…”
Section: Problem Statement and Mathematical Formulationmentioning
confidence: 99%
“…The efficient numerical technique is a more reliable tool for simulating the droplet evaporation process owing to its capability to consider the fully coupled mechanisms, like heat and mass transfer, thermal effects of substrate, evaporative cooling and thermocapillary convection [14,15]. In the present work, the effects of the substrate on Marangoni flow with respect to the influential parameters (thermal conductivity, thickness and substrate temperature) in a wide range are investigated.…”
Section: Introductionmentioning
confidence: 99%